Fuel consumption and pollutant emissions of spark ignition engines during cold-started drive cycles - Darnton, Nicholas Julian (1997)
This thesis details the development and evaluation of a procedure to predict the fuel consumption and pollutant emissions of spark ignition engines during cold-started drive cycles. Such predictions are of use in the early development and optimisation of an engine and vehicle combination with regard to legislated limits on vehicle performance over defined drive cycles. Although levels of pollutant emissions are the main focus of legislation, reducing fuel consumption is also of interest and drive cycle fuel consumption figures provide a useful benchmark of vehicle performance appraisals.